2016
DOI: 10.1371/journal.pone.0150555
|View full text |Cite
|
Sign up to set email alerts
|

Axial Spondylometaphyseal Dysplasia Is Caused by C21orf2 Mutations

Abstract: Axial spondylometaphyseal dysplasia (axial SMD) is an autosomal recessive disease characterized by dysplasia of axial skeleton and retinal dystrophy. We conducted whole exome sequencing and identified C21orf2 (chromosome 21 open reading frame 2) as a disease gene for axial SMD. C21orf2 mutations have been recently found to cause isolated retinal degeneration and Jeune syndrome. We found a total of five biallelic C21orf2 mutations in six families out of nine: three missense and two splicing mutations in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 47 publications
(49 reference statements)
3
31
0
Order By: Relevance
“…Patients in this family (A10) showed both RP and skeletal dysplasia, initially considered as unlinked traits. Again, our results prompted clinical re-evaluation, and supported C21orf2 association to this syndrome[26]. …”
Section: Resultssupporting
confidence: 71%
“…Patients in this family (A10) showed both RP and skeletal dysplasia, initially considered as unlinked traits. Again, our results prompted clinical re-evaluation, and supported C21orf2 association to this syndrome[26]. …”
Section: Resultssupporting
confidence: 71%
“…Consequently, C21orf2 was assessed in individuals with various ciliopathies; and homozygous and compound heterozygous mutations were identified in eight individuals with JATD from three families (Wheway et al, ). Recessive C21orf2 mutations were also identified in nine individuals from six different families with axial SMD (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported previously in nine homozygous and three compound heterozygous cases from four families of diverse ethnic backgrounds, and associated with variable phenotypes. Wang et al () reported homozygous mutations in four individuals from two families with axial SMD, all of whom had retinitis pigmentosa and short stature; three had hip dysplasia and two had a narrow thorax with short ribs. None had scoliosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations